Alexithymia in adults with brittle type 1 diabetes - Pelizza, Lorenzo; Pupo, Simona (Acta Biomedica Atenei Parmensis, 2019)
Background: The term “brittle” is used to describe an uncommon subgroup of patients with type 1 diabetes whose lives are disrupted by severe glycaemic instability with repeated and prolonged hospitalization. Psychosocial problems and emotional disturbances are the major perceived underlying causes of brittle diabetes. Aim of this study is (a) to assess alexithymia in patients with brittle and non-brittle diabetes, and (2) to examine its relationship with specific parameters of general psychopathology. Methods: Participants comprised 44 patients with brittle diabetes and a case-control group of 88 individuals with stable (non-brittle) diabetes, matched for age, gender, years of education, and diabetes duration. Alexithymia and general psychopathology were assessed using the “20-item Toronto Alexithymia Scale” (TAS-20) and the “Symptom Checklist-90-Revised” (SCL-90-R). Results: Patients with brittle diabetes were more alexithymic than the control group. Alexithymia scores showed significant correlations with SCL-90-R anxiety and somatization subscales, but were relatively independent from gender, education, diabetes duration and complications, depression and glycaemic control. Conclusions: Given the impact of alexithymia on type 1 diabetes, the early detection and intervention of alexithymic subjects are very important for a better outcome of diabetes.